Merging of oculomotor and somatomotor space coding in the human right precentral gyrus - Iacoboni, M (Brain (London, England : 1878), 1997)
Using PET and H215O, we investigated the cortical areas that merge two different ways of coding space in the cerebral cortex, those concerned with the oculomotor and the somatomotor space. Normal subjects performed a visuomotor task that required the spatial coding of visual stimuli in oculomotor space and of motor responses in somatomotor space. We manipulated the mapping of oculomotor and somatomotor space by instructing subjects to respond in half of the PET scans with uncrossed hands, i.e. each hand was in the homonymous hemispace (standard oculomotor-somatomotor mapping), and in the other half with crossed hands, i.e. with the left hand in the right hemispace and the right hand in the left hemispace (nonstandard oculomotor-somatomotor mapping). Reaction times were slower for crossed hands than uncrossed hands. Crossed hands produced increases in blood flow in the precentral and postcentral gyri of the right hemisphere. Increases in blood flow in the precentral gyrus were correlated with increases in reaction time comparing the crossed-hand task with the uncrossed one, whereas the increases in blood flow in the postcentral gyrus were not. These findings suggest that the right precentral gyrus merges oculomotor and somatomotor space coding in the human brain.